Pengaruh Permintaan Kredit Investasi Terhadap Pertumbuhan Ekonomi Dengan Interaksi Kebijakan Moneter di Provinsi Sulawesi Selatan - Anwar Ramli; Samsinar Samsinar (Seminar Nasional LP2M UNM, 2019)
This research is an attempt to identify, trace, analyze investment credit demand for growth with the interaction of monetary policy in Sulawesi Selatan. The purpose of this study is to look at the effect of demand for investment credit in economic growth with the interaction of monetary policy in the province of South Sulawesi. The type of data in this study uses secondary data, namely the source of data obtained from the publication of Bank Indonesia in the form of an annual report (BI) and the results of the publication of the Central Statistics Agency (BPS). The analytical method used is multiple linear regression functions to determine the effect or relationship of independent variables and dependent variables and data processing is done using SPSS Version 20 application tools. Based on the results of research that has been done, obtained: 1). Investment credit has a positive and significant effect on economic growth in South Sulawesi for the period 2006-2018. The presence of investment loans excites investors to hold and develop their investments without having to wait a long time for their personal capital to be collected but can easily submit credit requests to banks, 2). Investment credit has a positive and significant effect on economic growth with the interaction of monetary policy. The negative effect of interest rates on economic growth shows that changes in interest rates will affect aggregate expansion through investment changes. An increase in interest rates will reduce investment interest and reduce economic activity so that economic growth will contract. Based on the results of the research, it can be suggested that investment loans should be maintained and further increased. Because this credit is active in funding the economic sector in South Sulawesi in the long run.